Avoiding medical errors in general practice. Issue 4 (July 2015) - Coxon, Jonny; Rees, Jonathan
<x xml:space="preserve">Abstract</x> The two main types of error in general practice are diagnostic and prescribing errors. The authors consider how they might arise and suggest ways in which they may be avoided.